1993
DOI: 10.1108/00242539310043563
|View full text |Cite
|
Sign up to set email alerts
|

Managing Automation in Developing Countries: A Current View

Abstract: Outlines the advantages of automating libraries in developing countries and considers the problems relating specifically to finance, technology and management. Notes reliance on overseas aid and donations and points to local problems relating to maintenance and technology. Discusses availability of funds for maintenance, and of skilled staff to operate systems, and also organizational changes following automation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…It also can be concluded that most librarians in university libraries argue that computerisation should start with cataloguing. Mambo (1993) believes that in the developing countries, Note: Percentages are given in parentheses although computers will be required in all library activities, they should be deployed first to those areas where the service needs an immediate boost.…”
Section: Current Use Of Itmentioning
confidence: 99%
“…It also can be concluded that most librarians in university libraries argue that computerisation should start with cataloguing. Mambo (1993) believes that in the developing countries, Note: Percentages are given in parentheses although computers will be required in all library activities, they should be deployed first to those areas where the service needs an immediate boost.…”
Section: Current Use Of Itmentioning
confidence: 99%
“…The observed slow rate in IT applications in East Africa university libraries apart from shortage of qualified personnel was due to the costs involved. This was reflected by the amount of aid from international aid agencies or governments of the developed countries from the very initial stages of IT applications such as the purchase of computers and CD-ROM subscriptions (Mambo, 1993).…”
Section: Financial Constraintsmentioning
confidence: 99%
“…Raseroka (1993) reported that 83 per cent of university libraries owned microcomputers in Eastern and Southern African University libraries. Efforts to automate university library services in the university libraries surveyed largely started between 1987 to 1993 (Kimani, 1994;Mambo, 1993). However, during this formative period, the use of CD-ROMs was seen as an ideal first step towards library automation.…”
Section: Trends Towards Introduction Of It In East African Government-owned University Librariesmentioning
confidence: 99%